1988
DOI: 10.1161/01.hyp.11.6.657
|View full text |Cite
|
Sign up to set email alerts
|

Renal cortical and papillary blood flow in spontaneously hypertensive rats.

Abstract: SUMMARY The present study examined whether an alteration in renal medullary hemodynamics is associated with the development of hypertension in the spontaneously hypertensive rat (SHR). The relationships between whole kidney, cortical and papillary blood flows, and renal perfusion pressure were compared in 3-to 5-, 6-to 9-, and 12-to 16-week-old SHR and Wistar-Kyoto rats (WKY). Cortical and papillary blood flows were measured using a laser-Doppler flowmeter. Whole kidney and superficial cortical blood flows wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
55
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 22 publications
6
55
0
1
Order By: Relevance
“…The recent finding that papillary blood flow is reduced in SHR before the development of hypertension suggests that an elevation in renal medullary vascular resistance may participate in the development of this disease. 10 The present study examined whether structural changes or alterations in the vascular tone of the preglomerular vasculature of juxtamedullary nephrons could explain the decrements in renal medullary hemodynamics 11 and the pressure-natriuretic response in the kidney of SHR. 9 The results of the present study indicate that there are significant differences in the pressure-diameter relations in the preglomerular vasculature of juxtamedullary nephrons in SHR and WKY rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The recent finding that papillary blood flow is reduced in SHR before the development of hypertension suggests that an elevation in renal medullary vascular resistance may participate in the development of this disease. 10 The present study examined whether structural changes or alterations in the vascular tone of the preglomerular vasculature of juxtamedullary nephrons could explain the decrements in renal medullary hemodynamics 11 and the pressure-natriuretic response in the kidney of SHR. 9 The results of the present study indicate that there are significant differences in the pressure-diameter relations in the preglomerular vasculature of juxtamedullary nephrons in SHR and WKY rats.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, studies on the mechanism of pressurenatriuresis indicated that it is associated with changes in renal medullary hemodynamics, renal interstitial pressure, and inhibition of tubular reabsorption in deep nephrons. 1819 The present finding suggests that an elevated vascular tone in the preglomerular vasculature of juxtamedullary nephrons of SHR may account for the elevated renal medullary vascular resistance in this model of hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ' 2 In the SHR, the blunted pressure-natriuretic response is associated with a reduction in papillary blood flow 3 and renal interstitial hydrostatic pressure. 4 Recent studies by Gebremedhin et al 5 suggest that the decline in papillary blood flow in adult SHR is due to an enhanced vascular tone rather than structural changes in the preglomerular vasculature of the deep nephrons.…”
mentioning
confidence: 99%